1988
DOI: 10.2307/2095641
|View full text |Cite
|
Sign up to set email alerts
|

Incentives in Collective Action Organizations

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.. American Sociological Association is collaborating with JSTOR to digitize, preserve and extend access to American Sociological Review. The effects of members' interests in inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
195
0
3

Year Published

1999
1999
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 207 publications
(205 citation statements)
references
References 20 publications
(13 reference statements)
7
195
0
3
Order By: Relevance
“…Intra-organizational, rather than inter-organizational, coordination and awareness has been studied extensively, particularly in the context of groupware system use [1,14,19,23]. However for clarification, we reiterate here two key differences in our work from this existing research.…”
Section: Related Workmentioning
confidence: 89%
See 1 more Smart Citation
“…Intra-organizational, rather than inter-organizational, coordination and awareness has been studied extensively, particularly in the context of groupware system use [1,14,19,23]. However for clarification, we reiterate here two key differences in our work from this existing research.…”
Section: Related Workmentioning
confidence: 89%
“…In the context of interorganizational literature, our research is informed by two sets of theories regarding coordination between organizations: the first is collective action research on networks of organizations [19,22], and the second is exchange and resource dependency theories [35]. With regard to collective action research, we draw upon Marwell and Oliver's designation of collective action as actions surrounding "mutual interests and the possibility of benefits from coordinated action" [22].…”
Section: Related Workmentioning
confidence: 99%
“…Knoke and Wood (1981) found that the Purposive and Solidary incentives offered were significant predictors of an aggregate commitment index (a precursor to participation). Knoke (1988) found that Normative or Purposive incentives produce more commitment than any other type of incentive. Butterfoss et al (1996) found that higher benefits and lower costs predicted greater participatory roles assumed by committee members.…”
Section: Benefits and Costs Predicting Participationmentioning
confidence: 98%
“…For example, neighborhood organizations, economic interest groups, national voluntary associations (e.g., American Cancer Society), AIDS groups, self-help groups, and community coalitions have different goals. Because goals tend to be congruent with the incentives offered (Knoke, 1988), it is likely that these organizations will offer different incentives. In addition, certain groups (e.g., neighborhood organizations, economic interest groups) may attract members who are more interested in Personal benefits (e.g., improve the value of one's home), whereas groups such as community coalitions may have members who are interested in Normative benefits (e.g., prevent alcohol and other drug abuse).…”
Section: Type Of Organizationmentioning
confidence: 99%
“…Omitting theoretically important variables can therefore bias the statistical coefficients of included variables (King, Keohane, & Verba, 1994). Specifically, the model we use to analyze our data includes variables pertaining to the household economy, the social status of the households, benefits to households from CPRs, and the accessibility of state officials (Knoke, 1988;Verba et al, 1993). We rely on some of the more commonly discussed variables in the literature on governance of common pool forest resource in South Asia to operationalize the following empirical model.…”
Section: Studied Variables Data and Analytical Modelmentioning
confidence: 99%